Terorisme Dan Agama Dalam Perspektif Charles Kimball - Selvia Santi (Jurnal ICMES, 2017)
In this article the author tries to answer the research question, is it true that religion has encouraged terrorist groups to launch their acts of terror? To answer that, the author will use the thought of a comparative religious scholar who once served in the conflict areas of the Middle East, Charles Kimball, which is described in his book "When Religion Becomes Evil". Kimball used a historical, cultural, and political approach to explain his thought about relation between religion and violence. He identified five signs that people have to be alert; the signs when religious understanding has deviated so that it will bring disaster. These five signs are absolute truth claims, blind obedience, establishing the "ideal" time, the end justifies any means, and declaring holy war. The conclusion that can be drawn is that terrorist actors basically only use religion as a justification for their actions.